Work anxiety as a mediator on the relationship between inclusive leadership and turnover intention among high school teachers - Liang, Huang; Omar, Muhd Khaizer; Yang, Bai; Qibin, Zhang (Human Resources Management Academic Research Society (HRMARS), 2024)
This study examines the mediating role of work anxiety on the relationship between inclusive leadership and turnover intention among high school teachers in Wuhan, China. The sample consists of 407 educators from the public schools. Data were analyzed using correlation analysis and mediation effect analysis. The study proposes the following alternative hypotheses: H1, more inclusive leadership styles reduce job anxiety among high school teacher; H2, more inclusive leadership styles decrease teachers' turnover intentions; and H3, work anxiety mediates the relationship between inclusive leadership styles and teachers' intention to leave their jobs.